La recepción de Cleomedes en los primeros años paleólogos: El Ms. Bruxelles, Bibliothèque Royale Albert I, 4476-78 - Caballero-Sánchez, Paula María (Byzantion (Peeters), 2022)
Cleomedes’ Caelestia was the main work used by Byzantine scholars to learn Greek astronomy. The text is preserved in circa one hundred manuscripts, most of them dating from the Palaiologan era (1261-1453), during which Cleomedes was widely copied and studied. The Bibliothèque royale Albert I, 4476-78 is one of the Palaiologan volumes which contains the Caelestia: a recueil factice which shows the revival of Cleomedes from the very first decades of the Palaiologan era. This paper provides a comprehensive analysis of the codex from a codicological and palaeographical point of view and proposes an accurate dating of the several codicological units of the volume, focussing on Cleomedes unit. Indeed, this paper states that Cleomedes’ copy can be placed in the third decade of the 13th century according to palaeographical criteria. Therefore, this manuscript was copied some decades earlier than the planudean codex Edinburgh, National Library of Scotland, Advocates Library ms. 18.7.15.
Keywords: Paleografía griega; Astronomía griega; Ancient Greek Astronomy; Cleomedes; Byzantine Studies; Byzantine scholarship; Greek Palaeography